Petrologia e geocronologia (U-Pb) da suíte Caapucú – Sul do Paraguai : magmatismo pós-tectônico relacionado à evolução de uma faixa móvel brasiliana - Leite, Amanda Figueiredo Granja Dorilêo (2018)
The Caapucú Magmatic Suite (CMS), the focus of this study, includes Precambrian rocks that form the High Caapucú Block, located at the northern edge of the Rio de La Plata Craton in southern Paraguay. This is an acidic plutonic to volcanic magmatic suite, represented by metavolcanic-sedimentary rocks of the Paso Pindó Group, which are in tectonic contact with the Villa Florida Metamorphic Suite of the High Caapucú Block. Based on the field and petrographic data of the CMS, plutonic and volcanic lithotypes of this suite were identified, characterized and grouped into four petrographic facies: the Rapakivi porphyritic syenogranite facies (RPSF), the monzogranite to alkali-feldspar microgranite facies (MAMF), the rhyolite facies (RF) and the ignimbrite facies (IF). These are undisturbed rocks of primarily syenogranitic composition with very-fine-tomedium grained crystals and inequigranular-to-porphyritic granophyric textures. The facies show circular-to-ring configurations with a large difference in relief in the area in which hypabyssal facies are partly surrounded by volcanic facies. Lithochemical analysis shows a limited compositional variation within this suite, which may be classified as acidic rocks, according to a silica content ranging from 73.9 to 79.2%. This corresponds to A-type granitoids that formed from non-tholeiitic, metaluminous-to-slightly peraluminous ferrous magmatism in a post-collisional magmatic arc environment. The U-Pb geochronological (Laser Ablation-Inductively Coupled Plasma-Mass Spectrometry (LA-ICPMS)) data collected from zircon crystals suggest magma crystallization ages for the RPSF and IF of 543 ± 7.3 Ma and 553.1 ± 5.4 Ma, respectively. Based on these data, magmatism of the CMS likely originated from a Neoproterozoic mobile belt generated by agglutination of the Paranapanema and Rio de La Plata cratons. The CMS presumably developed in the post-collisional stage of the Brazilian/Pan-African Cycle during the formation of Western Gondwana. Considering the lithostratigraphic and structural framework of the CMS, in addition to the collection of geochronological ages presented here and those previously available, the tectonic-magmatic correlation between the CMS and the post-tectonic igneous events of the Ribeira and/or Dom Feliciano belts of the Mantiqueira Province is suggested.